Comparison of 5-Year Clinical Results of Descemet and Non-Descemet Stripping Automated Endothelial Keratoplasty. Issue 5 (May 2020) - Omoto, Takashi; Toyono, Tetsuya; Inoue, Tatsuya; Shirakawa, Rika; Yoshida, Junko; Miyai, Takashi; Yamagami, Satoru; Usui, Tomohiko
Abstract : Purpose: To compare 5-year clinical results of non-Descemet stripping automated endothelial keratoplasty (nDSAEK) and DSAEK. Methods: A retrospective chart review involving patients with non–Fuchs-type bullous keratoplasty who underwent nDSAEK or DSAEK 5 years before the review was performed on demographics, graft survival rate, endothelial cell density (ECD), best-corrected visual acuity (BCVA), and complications. Results: Fifty eyes (nDSAEK 28, DSAEK 22) were included in this study. Common indications for surgery were bullous keratopathy due to glaucoma, cataract surgeries, or laser iridotomy. The graft survival rates in nDSAEK and DSAEK eyes at 1, 3, and 5 years were 0.75 and 0.86, 0.67 and 0.81, and 0.59 and 0.74, respectively. The mean donor ECDs of nDSAEK and DSAEK eyes were 2638 and 2503 cells/mm 2, respectively; these decreased to 1654 and 1406, 1503 and 1218, and 1108 and 1020 cells/mm 2 at 1, 3, and 5 years, respectively. The mean preoperative BCVAs of nDSAEK and DSAEK eyes were 1.08 and 1.11 LogMAR, respectively; these improved to 0.238 and 0.190, 0.126 and 0.157, and 0.097 and 0.070 LogMAR at 1, 3, and 5 years, respectively. The most common complication was intraocular pressure elevation. There were no statistically significant differences between nDSAEK and DSAEK in graft survival rates, changes in ECD and BCVA, or the occurrence of postoperative complications, with the exception of the change in ECD at 2 years (1173 and 1193 cells/mm 2, P = 0.0159). Conclusions: Our 5-year clinical results of nDSAEK and DSAEK did not show significant differences at almost all points.